PENGUATAN DIGITALISASI MARKETING UNTUK MENINGKATKAN PENJUALAN PADA PELAKU UMKM PEREMPUAN DI KOTA MEDAN, SUMATERA UTARA - Erwansyah Erwansyah; Rintan Saragih; Truly Okto H. Purba (Universitas Methodist Indonesia, 2022)
Digital marketing plays an important role for MSMEs in marketing their products so that later it is expected to be able to increase sales. This condition also results in consumer changes in fulfilling lifestyles. In order to continue to increase this contribution and participation, MSMEs are required to be involved in digital platforms. The digital world is expected to become a crucial thing for business activities. Digital marketing is promotional activities as well as market search carried out through digital media. The use of digital marketing must immediately be responded positively by MSMEs, especially women MSMEs located in the city of Medan. From the initial mapping it is known that the majority of these MSME actors do not yet have a website. Promotional activities are carried out only through Facebook, Instagram and Tik Tok. Only one MSME actor was identified as having a website. With this service activity, it is hoped that more specific identification of problems and constraints in selling MSME products can be carried out. In addition, through this activity, the team will educate and introduce product marketing methods through the use of digital marketing media to increase market share and reach consumers more broadly. It is important to note that MSME actors must carefully analyze the market context in which the business operates, identify opportunities, and then plan how to compete effectively.